Diversity in the Classroom : Finnish Student Teachers' Perceptions Towards Teaching in an Inclusive Environment - Iivonen, Anni (My University, 2024)
This thesis examines Finnish student teachers’ perceptions of inclusion by investigating their attitudes, concerns, and attributing tendencies. To get a vast understanding of the perceptions mixed method research was conducted. The quantitative part of the research was executed using the Sentiment, Attitudes, and Concerns about Inclusive Education Revised (SACIE-R) scale. The Method of Empathy Based Story (MEBS) was performed to provide the qualitative part of this research. The results show that student teachers' attitudes tend to be close to neutral or even negative towards inclusive education and they have many concerns about teaching in an inclusive environment. They were more negative about having (certain) students with special needs in their classrooms than towards the general idea of diverse students being in regular classes. The concerns were about their ability to provide a peaceful learning environment without conflicts where everyone would get the support they need and reach their learning goals. In addition, having enough resources and help from other educators caused concerns. Furthermore, when asked about improvements regarding inclusive education, the student teachers suggested mostly inclusive measures. However, few discords were found where inclusion was rejected and segregative measures were proposed. The results also showed that the student teachers have a self-serving bias when inclusive education is successful, meaning that when everything went well, it was seen to be the teacher’s achievement rather than giving any credit to the students. These findings suggest that the student teachers’ perceptions towards inclusion are close to negative even though the recommended measures were quite inclusive. Further research is needed to investigate what measures teachers use in their inclusive classrooms and if they support or contradict inclusion. In addition, it would be important to find out where the negative perceptions of student teachers stem from.
Keywords: inclusion, inclusive education, diversity, equality, equity, teacher training, student teachers, perceptions, attitudes, concerns, attribution